Man as the Object of the Social Sciences - Barrette, Antonio (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1948)
We are pleased to publish an address presented by the Honourable Antonio Barrette, Minister of Labour for the Province of Quebec, on the occasion of receiving an honorary doctorate in Social Sciences, at the University of Montreal, the 28th of May, 1948.